Evaluation of children with protein energy malnutrition and level of malaria parasitemia in Kwara State, Nigeria (Annals of African Medical Research, 2018)
Malaria and Protein-Energy-Malnutrition (PEM) are two major causes of childhood mortality in sub-Saharan Africa. Malaria can predispose a child to PEM and the reverse may also be true. Recent studies have presented inconsistent findings about nutritional status and the occurrence of malaria among the children. The goal of this study was to evaluate the association between PEM and malaria parasitemia if any. A case control study in which 90 children diagnosed for PEM (aged 6-59 months), and another well-nourished 90 children age and sex-matched controls were evaluated for malaria parasitemia. A semi-structured proforma was used to obtain relevant information on the children’s sociodemographic characteristics, nutritional indices amongst others. Venous blood sample was collected and thick and thin blood film were prepared and viewed under the microscope. Malaria parasitemia was present in 82 (91.1%) of malnourished group and 12 (13.3%) of the well-nourished group (P